2015
DOI: 10.1089/sur.2014.097
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Skin Preparation and Draping in Modern Total Joint Arthroplasty: Current Evidence

Abstract: The importance of skin preparation and adequate and reliable draping cannot be overemphasized for infection prevention, especially in clean operations such as THR and TKR. Thorough and strict protocols are mandatory for every department, as well as education curricula for operating room personnel. Further randomized studies are mandatory to specify the effect of the above measures, their pitfalls, and their improvement, along with further crucial details such as cost-benefit analysis of different pre-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Recent evidence advocates for dual‐agent skin antiseptics (eg, CHG and PI) rather than a single agent . Antiseptic agents in combination with alcohol were found to be the most effective in reducing skin contaminants . A literature review by Privitera showed that skin preps that included a combination of CHG and alcohol are effective because the alcohol is fast‐acting and the CHG provides a longer residual effect for reduction of microbes.…”
Section: Strategies To Prevent Ssismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence advocates for dual‐agent skin antiseptics (eg, CHG and PI) rather than a single agent . Antiseptic agents in combination with alcohol were found to be the most effective in reducing skin contaminants . A literature review by Privitera showed that skin preps that included a combination of CHG and alcohol are effective because the alcohol is fast‐acting and the CHG provides a longer residual effect for reduction of microbes.…”
Section: Strategies To Prevent Ssismentioning
confidence: 99%
“…Perioperative personnel create and maintain the sterile field and perform the skin preparation. After the perioperative nurse or designee completes the antimicrobial cleansing of the surgical site, the scrubbed team members drape the surgical area with sterile towels and sheets to provide a sterile area for execution of the surgical procedure …”
mentioning
confidence: 99%
“…Therefore, it is difficult to ascertain the effects of chlorhexidine-based agents on the prevention of PJI in primary THA patients based on the results of previous studies. At present, the strength of the evidence for preoperative chlorhexidine bathing for the prevention of PJI after primary THA remains uncertain, and there is a lack of consistent suggestion and consensus in the relevant literature [ 26 , 27 , 28 , 29 ]. To the best of our knowledge, this comparative study is the first to specifically investigate the effects of preoperative chlorhexidine bathing on reducing the incidence rate of PJI after primary THA.…”
Section: Introductionmentioning
confidence: 99%
“…7 Iodophor impregnated adhesive dressings, such as Ioban are commonly used in shoulder surgeries as a part of the sterile draping process. 12,13 One study regarding hip procedures showed that using this type of drape caused a statistically significant reduction in the number of bacteria at the surgical site. 12 It is often noted during the authors' operative cases that there are grossly visible particles present on the adhesive surface of the dressing following removal of the dressing.…”
Section: Introductionmentioning
confidence: 99%